The high energy X-ray probe (HEX-P): studying extreme accretion with ultraluminous X-ray sources - Bachetti, Matteo; Middleton, Matthew J.; Pinto, Ciro; Gúrpide, Andrés; Walton, Dominic J.; Brightman, Murray; Lehmer, Bret; Roberts, Timothy P.; Vasilopoulos, Georgios; Alford, Jason; Amato, Roberta; Ambrosi, Elena; et al. (Frontiers in Astronomy and Space Sciences, 2023)
Introduction: Ultraluminous X-ray sources (ULXs) represent an extreme class of accreting compact objects: from the identification of some of the accretors as neutron stars to the detection of powerful winds travelling at 0.1–0.2 c, the increasing evidence points towards ULXs harbouring stellar-mass compact objects undergoing highly super-Eddington accretion. Measuring their intrinsic properties, such as the accretion rate onto the compact object, the outflow rate, the masses of accretor/companion-hence their progenitors, lifetimes, and future evolution-is challenging due to ULXs being mostly extragalactic and in crowded fields. Yet ULXs represent our best opportunity to understand super-Eddington accretion physics and the paths through binary evolution to eventual double compact object binaries and gravitational-wave sources. Methods: Through a combination of end-to-end and single-source simulations, we investigate the ability of HEX-P to study ULXs in the context of their host galaxies and compare it to XMM-Newton and NuSTAR, the current instruments with the most similar capabilities. Results: HEX-P’s higher sensitivity, which is driven by its narrow point-spread function and low background, allows it to detect pulsations and broad spectral features from ULXs better than XMM-Newton and NuSTAR. Discussion: We describe the value of HEX-P in understanding ULXs and their associated key physics, through a combination of broadband sensitivity, timing resolution, and angular resolution, which make the mission ideal for pulsation detection and low-background, broadband spectral studies.